Analisis Penerapan SAK EMKM Pada UMKM Fantastic Phone Gadget and Computer di Gunung Kidul - Risky Ayu Lestari; Diska Arliena Hafni (CV. Ulil Albab Corp, 2024)
This research aimed to analyze the application of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in Fantastic Phone Gadget and Computer MSMEs in Ngawen District, Gunungkidul Regency, Yogyakarta. This study used a qualitative method with a descriptive approach. Data was collected using observation, documentation, and interview techniques. Data analysis was then carried out using descriptive analysis techniques which began by describing the phenomena experienced by the research subjects, then analyzing using existing theories. The findings showed that Fantastic Phone Gadget and Computer has not prepared financial reports by SAK EMKM; they only prepared income and out cash records. The inhibiting factors for implementing SAK EMKM on Fantastic Phone Gadget and Computer consist of internal and external factors; some of the internal factors that become obstacles are the lack of understanding of accounting by the finance department, the lack of trained human resources, and time constraints. Meanwhile, the external factor is the absence of training or guidance on implementing SAK EMKM from the MSME service.